6. Cytotoxic Potential of n-Hexane Extract of Calotropis gigantea L. Leaves - Kartini Hasballah; Murniana Murniana; Al Azhar; Nurul Rahmi (The International Journal of Tropical Veterinary and Biomedical Research, 2016)
The present study was done to determine the cytotoxic potential of n-hexane extract of Calotropis gigantea L. leaves and its fractions. Here, dried leaves of C. gigantea L. were macerated using n-hexane to obtain crude extract of 21.16 g (1.03%). The components of n-hexane extract of C. gigantea L. leaves were separated with vacuum-liquid chromatography resulted 4 fractions which are A (0.5 g), B (0.9g), C (5.29 g), and D (6.25 g). Phytochemical screening indicated that the extract contained various secondary metabolic compounds such as steroids, terpenoids, saponins, flavonoids, coumarins, and phenolics. Cytotoxic potenital of the crude extract of C. gigantea L. and its fractions was examined using brine shrimp lethality test (BSLT). The LC50 values of C. gigantea’s n-hexane extract and its fractions that determined by Finney method were 272.27 (n-hexane extract), 31.62 (fraction A), 43.65 (fraction B), 33.89 (fraction C) and 20.98 (fraction D) ?g/mL, respectively. The most active was D fraction contained terpenoids, flavonoids, and phenolics which were assumed contribute to its cytotoxic potential. These results suggested that n-fraction of C. gigantea might possess antitumor or pesticidal activities..